PILATES EXERCISE LEBIH EFEKTIF MENINGKATKAN FLEKSIBILITAS LUMBAL DIBANDINGKAN SENAM YOGA PADA WANITA DEWASA - Luh Putu Ayu Vitalistyawati; I Wayan Weta; Muthiah Munawaroh; Ida Bagus Ngurah; I Putu Adiartha Griadhi; Muh. Ali Imron (Sport and Fitness Journal, 2018)
Introduction: Productive women who’s working in static potition can cause stiffness back muscle. The stiffness of back muscle can decrease lumbal flexibility. When lumbal flexibility was decreased, it can cause low back pain during activities. Yoga and pilates exercise are recommended program for increase lumbal flexibility.. Purpose: This study aims to prove the pilates exercise is more effective to increase lumbal flexibility comparing with yoga on adult woman. Method: Design of this study uses research methods experimental study pre and post test design. Total sampel of this research study are 30 adult women at Banjar Kelod Ungasan, whose age are 30-45 years old and have 0-20 cm flexibility score. The sampel devided into two groups which the group I (n=15) was given pilates exercise ,while group II (n=15) was given yoga twice a week in 6weeks. This research was using sit and reach test as measured flexibility. Result: Based on Paired Sample t-Test statistical analysis the results of this study research shown that the difference in the mean of lumbal flexibility in group I was obtained 21.34±3.13cm with p<0.001 , while the mean of lumbal flexibility in group II was obtained 19.11±2.39cm with p<0.001. The difference lumbal flexibility in group I and group II was obtained 5.36±1.48cm with p<0.001. Conclusion: The conclusion that the pilates exercise was more effective to increase lumbal flexibility comparing with yoga on adult woman.